Developing new generation of educational leaders for world class university - Hassan, Zaharah; Silong, Abu Daud; Ismail, Ismi Arif; Asmiran, Soaib (Elsevier, 2011)
The purpose of this study is to explore the meanings of being World Class University (WCU) and roles and competencies of new generation of educational leaders leading WCU. The data are collected through the qualitative methods of three focus group and eight in-depth interviews of professors. The interviews were recorded, transcribed verbatim, coded and analyzed according to themes. The findings indicated some of the difficulties in defining WCU, the importance of research excellence in WCU and the effect of globalization and internationalization. Findings indicated that we do need a new generation of leaders with certain traits, competencies and playing various leadership roles.